Keterampilan Menulis dan Efikasi Diri Siswa melalui Model Cooperative Integrated Reading and Composition (CIRC) dengan Menggunakan Media Seri Bergambar - Sisleni Sisleni; Dian Susyla; Apriza Fitriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the differences between the CIRC model with pictorial series media, CIRC without media, and conventional learning on the writing skills and self-efficacy of students at SMK Negeri 3 Kepahiang. This study used a quantitative approach with a quasi-experimental design. The results showed differences in writing skill improvement in each class. The class with the CIRC model with pictorial series media experienced the highest improvement, from a pretest average of 25.69 to 82.41 on the posttest. The CIRC class without media increased from 28.97 to 65.34, while the conventional class increased from 27.06 to 59.71. In conclusion, there are differences in students' writing skills and self-efficacy. The CIRC class with pictorial series media significantly differs from the CIRC class without media and the conventional class. Overall, there are differences in learning outcomes in each class, indicating variations in the effectiveness of the treatment. Keywords: CIRC, Self-Efficacy, Pictorial Series Media, Writing Skills, Quasi-Experimenta